Customer helping and advocacy behaviours within dyadic financial service relationships: a gift-giving perspective - van Tonder, Estelle; Saunders, Stephen Graham; Mwavita, Mwarumba; Kim, Sohee (International journal of bank marketing, 2022)
PurposeThis study aims to examine customer helping and advocacy behaviours within dyadic financial service relationships involving customers and fellow customer helpers.Design/methodology/approachThe gift-giving literature was used to propose a customer-to-customer interaction model, which was tested and cross-validated among electronic banking customers in South Africa (n = 404) and Australia (n = 244). Self-administered questionnaires were distributed to respondents who are users of electronic banking services and who previously received help with the service from a fellow customer. Data analysis included multi-group structural equation modelling.FindingsThe findings support the view that selected source credibility dimensions may influence greater affective commitment towards fellow customer helpers at various levels. Subsequently, further altruistic gift-giving in the form of customer helping and advocacy behaviours may result from higher levels of affective commitment. Feeling secure in their relationships with fellow customer helpers, customer recipients of help are likely to further socialise other customers who may share a common interest in the service category (e.g. electronic banking), but do not necessarily support the financial service provider of the customer.Originality/valueThe findings extend the conceptual domain of affective commitment and shed light on the factors contributing to the development of strengthened bonds between customers and fellow customer helpers within dyadic financial service relationships. Additionally, greater financial service socialisation and use may be achieved when the helping and advocacy behaviours of customer helpers are not restricted to a specific service provider. Subsequently, the current investigation advances knowledge of the underlying processes involved in motivating these desired service outcomes and behaviours.